2020
DOI: 10.1155/2020/9043806
|View full text |Cite
|
Sign up to set email alerts
|

Sesamol Protects Testis from Ischemia-Reperfusion Injury through Scavenging Reactive Oxygen Species and Upregulating CREMτ Expression

Abstract: Testicular torsion/detorsion-induced damage is considered as a typical ischemia-reperfusion injury attributed to excessive reactive oxygen species (ROS) production. ROS may regulate many genes whose expression affects cell-cycle regulation, cell proliferation, and apoptosis. The cAMP-responsive element modulator-τ (CREMτ) gene expression in the testis is essential for normal germ cell differentiation. The present study was aimed at investigating the effect of sesamol, a powerful antioxidant, on testicular isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Sixty rats were randomly divided into 3 experimental groups ( n = 20 per group): group A = sham-operated control; group B = testicular ischemia-reperfusion; and group C = testicular ischemia-reperfusion treated with salidroside. The surgical procedure was conducted in accordance with our previously described method [ 31 ]. Operation was carried out with ketamine (50 mg/kg, intraperitoneal) anesthesia under aseptic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Sixty rats were randomly divided into 3 experimental groups ( n = 20 per group): group A = sham-operated control; group B = testicular ischemia-reperfusion; and group C = testicular ischemia-reperfusion treated with salidroside. The surgical procedure was conducted in accordance with our previously described method [ 31 ]. Operation was carried out with ketamine (50 mg/kg, intraperitoneal) anesthesia under aseptic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Parihar et al showed that intraperitoneal administration of 50 mg/kg sesamol before gamma‐irradiation to the whole body could protect mice against weight loss and mortality rate 27 . Wei et al demonstrated that sesamol could protect rat testis from ischemia–reperfusion damage by reducing ROS and upregulating expression of cAMP‐responsive element modulator‐τ (CREMτ) in the testis which is necessary for normal germ cell differentiation 38 . Gao et al reported that sesamol had protective effects and reduced apoptosis in focal cerebral ischemia by increasing Bcl‐2 protein and decreasing Bax protein 39 …”
Section: Discussionmentioning
confidence: 99%
“…27 Wei et al demonstrated that sesamol could protect rat testis from ischemia-reperfusion damage by reducing ROS and upregulating expression of cAMP-responsive element modulator-τ (CREMτ) in the testis which is necessary for normal germ cell differentiation. 38 Gao et al reported that sesamol had protective effects and reduced apoptosis in focal cerebral ischemia by increasing Bcl-2 protein and decreasing Bax protein. 39 ROS levels and antioxidant compounds must be balanced by pro-oxidant and antioxidant agents, otherwise, ROS over-production leads to oxidative stress that can affect the female reproductive system.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were randomly divided into three groups of twenty rats per group, group 1: sham-operated control; group 2: testicular ischemia-reperfusion; and group 3: testicular ischemia-reperfusion + salvianolic acid B treatment. The surgical procedure was performed according to our previously described method [ 25 ]. An intraperitoneal injection of ketamine (50 mg/kg; Sigma Chemical Company, St. Louis, MO, USA) was used for general anesthesia in each rat.…”
Section: Methodsmentioning
confidence: 99%
“…Testicular spermatogenic evaluation was conducted as described previously [ 25 ]. Testicular weight, seminiferous tubular diameter, germ cell layer number, and Johnsen's score were used to evaluate testicular spermatogenesis.…”
Section: Methodsmentioning
confidence: 99%